DECONSTRUCTING BEETHOVEN'S PIANO SONATA NO.15 WITH SCHENKERIAN THEORY - Doe, Jane Elizabeth; Garcia, Maria Sofia (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This paper uses Schenkerian analysis to explore the Beethoven Piano Sonata No.15 in D Major, Opus 28, focusing on the exposition sections of the first movement. Schenkerian theory is an analytical method developed by Austrian composer and theorist Heinrich Schenker. This theory can provide a deeper understanding of a piece's musical content by revealing its underlying structure. The relationship between theory and performance will be discussed to provide a more comprehensive analysis. This paper also demonstrates how Schenkerian analysis can illuminate the characteristics of Beethoven's music and influence how we hear his music. Through this analysis, we can better understand this work and appreciate its complexity.